Web-Based IoT Smart Door Lock System for Secure Building Access Management - Nordin, Umi Umairah; Nayef Aldulwahab Mohammed Alduais (Applied Information Technology And Computer Science, 2025)
This project showcases the successful creation and execution of a secure IoT-based Smart Door Access System designed to improve access control and user management in intelligent environments. The system incorporates essential features such as user registration, login, profile management, password recovery, door access monitoring, and access logs. By employing RFID technology alongside the ESP8266 microcontroller, it guarantees secure and effective authentication. The backend is constructed using the Laravel web framework integrated with a MySQL database, while real-time data visualization is facilitated through ThingSpeak The system comprises extensive modules for door monitoring and control, user administration, report generation, and profile management. All project goals have been thoroughly met, and the final functioning prototype successfully merges both hardware and software elements. The system exhibits excellent performance in managing door access, delivering real-time updates, and ensuring precise access records. This solution provides a scalable and reliable method for securing entry points in office settings, educational institutions, and various smart facilities.